2006
DOI: 10.1038/ng1693
|View full text |Cite
|
Sign up to set email alerts
|

Physiogenomic resources for rat models of heart, lung and blood disorders

Abstract: Cardiovascular disorders are influenced by genetic and environmental factors. The TIGR rodent expression web-based resource (TREX) contains over 2,200 microarray hybridizations, involving over 800 animals from 18 different rat strains. These strains comprise genetically diverse parental animals and a panel of chromosomal substitution strains derived by introgressing individual chromosomes from normotensive Brown Norway (BN/NHsdMcwi) rats into the background of Dahl salt sensitive (SS/JrHsdMcwi) rats. The profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 27 publications
3
41
0
Order By: Relevance
“…The present studies highlighted that CSS panels, although capable of revealing some complex disease associations (15,30), lacked the breadth to identify distant interacting genetic factors characteristic of a complex disease like ARD. RNA-Seq allows for more complete documentation of genetic changes relevant to complex disease etiology (31).…”
Section: Discussionmentioning
confidence: 99%
“…The present studies highlighted that CSS panels, although capable of revealing some complex disease associations (15,30), lacked the breadth to identify distant interacting genetic factors characteristic of a complex disease like ARD. RNA-Seq allows for more complete documentation of genetic changes relevant to complex disease etiology (31).…”
Section: Discussionmentioning
confidence: 99%
“…We also compared our microarray data against available in vivo lung tissue-based PH microarray studies reported in PubMed, representing work across a variety of species (human, mouse, rat) (10,11,18,29). For example, one previous study utilized for comparison included significantly differentially expressed genes between normoxia and hypoxia conditions for male Dahl SS rats (29). A list of significantly differentially expressed genes in Homo sapiens diagnosed with PH was taken from Table 3 and Supplemental Table S1 from a study by Geraci et al (10).…”
mentioning
confidence: 99%
“…86-90 Physiogenomics has also been successfully applied in rodent animal models by others. 63 Here we demonstrated that physiogenomics also applies to sensorial stimuli, specifically acoustic patterns, as exemplified by the oddball task. Consistent with a targeted, hypothesis-driven query, we compared genes involved in dopaminergic and serotonergic neurotransmitter systems and determined a high level of association to DBH and DRD4, which is supported by prior pathophysiological and genetic associations to schizophrenia and uncovered a new association to HTR3A.…”
Section: Discussionmentioning
confidence: 80%